S-acylation of a geminivirus C4 protein is essential for regulating the CLAVATA pathway in symptom determination. (20th June 2018) - Li, Huiyun; Zeng, Runxiu; Chen, Zian; Liu, Xiaoshi; Cao, Zhendan; Xie, Qi; Yang, Chengwei; Lai, Jianbin
Abstract : S-acylation of the beet severe curly top virus C4 protein is essential for its membrane association, interaction with CLV1, and symptom determination during geminivirus infection. Abstract: Geminiviruses, such as beet severe curly top virus (BSCTV), are a group of DNA viruses that cause severe plant diseases and agricultural losses. The C4 protein is a major symptom determinant in several geminiviruses; however, its regulatory mechanism and molecular function in plant cells remain unclear. Here, we show that BSCTV C4 is S-acylated in planta, and that this post-translational lipid modification is necessary for its membrane localization and functions, especially its regulation of shoot development of host plants. Furthermore, the S-acylated form of C4 interacts with CLAVATA 1 (CLV1), an important receptor kinase in meristem maintenance, and consequentially affects the expression of WUSCHEL, a major target of CLV1. The abnormal development of siliques in Arabidopsis thaliana infected with BSCTV is also dependent on the S-acylation of C4, implying a potential role of CLAVATA signaling in this process. Collectively, our results show that S-acylation is essential for BSCTV C4 function, including the regulation of the CLAVATA pathway, during geminivirus infection.